Mining for Posttraumatic Growth (PTG) in Sexual Minority Women Who Survive Intimate Partner Violence: A Conceptual Perspective. - Counselman-Carpenter, Elisabeth; Redcay, Alex (Behavioral Sciences, 2018)
This theoretical paper explores the need to use posttraumatic growth (PTG) as a framework when studying sexual minority women (SMW) who are survivors of intimate partner violence (IPV) to examine the relationship between risk factors such as stress, anxiety and alcohol use and to understand the role of protective factors through mining for the presence of posttraumatic growth (PTG). Despite a call for continued research in this highly vulnerable population, representative studies of SMW and PTG remain extremely limited. Research that examines the relationship between IPV, behavioral health issues, and posttraumatic growth would provide the opportunity to develop tailored intervention models and opportunities for program development to decrease isolation and increase factors of posttraumatic growth. In particular, the impact of how interpersonal relationships as potential mediators and/or outcomes of posttraumatic growth (PTG) needs to be explored more thoroughly. PTG is a valuable framework for vulnerable populations such as sexual minority women because it focuses on how transformative change may result from traumatic experiences such as surviving IPV.
Keywords: Intimate partner violence; Post-traumatic growth; Sexual minority women; dept.swk; intimate partner violence; peer-reviewed; sexual minority women